Adsorption–desorption behavior of the hydrophobically associating copolymer AM/APEG/C-18/SSS. Issue 22 (18th April 2019) - Quan, Hongping; Lu, Qiangying; Chen, Zhonghao; Huang, Zhiyu; Jiang, Qingying
Abstract : In this study, the acrylamide, allyl polyethylene-1000, octadecyl dimethyl allyl ammonium chloride, and sodium styrene sulfonate were chosen to synthesize a quadripolymer which with a hydrophobic association existed between molecules. Abstract : In this study, acrylamide (AM), allyl polyethylene-1000 (APEG), octadecyl dimethyl allyl ammonium chloride (DMDAAC-18), and sodium styrene sulfonate (SSS) were chosen to synthesize a quadripolymer (HPAAT) in which a hydrophobic association exists between the molecules. The critical concentration of the hydrophobic association was determined using fluorescence spectrophotometry. Furthermore, HPAAT formed films by adsorbing onto a carbonate rock surface. The molecular structure of HPAAT was characterized using Fourier-transform infrared spectroscopy and 1 H-NMR spectroscopy, the results showed that the obtained product was consistent with the target product. The intrinsic viscosity was determined using an Ubbelohde viscometer. The molecular weight and dispersion exponent of HPAAT were determined using gel permeation chromatography. Addition of HPAAT into 20% HCl decreased the reaction rate of the acid rock obviously, even at a low viscosity. Variation of the reaction rate with time with different amounts of HPAAT was investigated using the volume of carbon dioxide gas produced. The adsorption and desorption of HPAAT on a carbonate rock surface were demonstrated using infrared spectroscopy analysis, scanning electron microscopy and ultraviolet spectrophotometry.